Sovereign bodies : citizens, migrants, and states in the postcolonial world - Hansen, Thomas Blom, 1958-; Stepputat, Finn (Anthropology online., 2005)
9/11 and its aftermath have shown that our ideas about what constitutes sovereign power lag dangerously behind the burgeoning claims to rights and recognition within and across national boundaries. New configurations of sovereignty are at the heart of political and cultural transformations globally. Sovereign Bodies shifts the debate on sovereign power away from territoriality and external recognition of state power, toward the shaping of sovereign power through the exercise of violence over human bodies and populations.